تحليل بعض مؤشرات الشمول المالي واثارها على القروض المتعثرة في العراق للمدة(2011- 2021) - كشكول عادل سلام; بحيت غالب شاكر (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
The research deals with some indicators of financial Comprehensive that would affect non-performing loans within the scope of the Iraqi economy، and the most important determinants and obstacles that have a direct or indirect role on the effectiveness of economic policies related to the above have been highlighted. It harmonizes the indicators of financial Comprehensive، and thus its reflection on the credit risks of the banking sector in its overall form. As for the importance of the research and its goal، it focused on diagnosing the reality of the Iraqi banking sector and the opportunities and challenges related to the level of financial services، and within a scope related to the limits of the spatial research associated with Iraq as a case study and the temporal limits 2011- 2021، as for the conclusions، the banking default was considered a basic determinant to reach this financial and economic stability، in addition to that the indicators of financial inclusion in Iraq showed very low rates، which negatively affected the achievement of financial stability policies in particular، and at the level of the national economy in general، and there is no doubt that the high percentages Lagging loans correspond to the low indicators of financial inclusion. The research concluded its recommendations، the most important of which is focusing on productive loans، reducing consumer loans as much as possible، relying on electronic services and strengthening financial inclusion tools.